The Effect Of Brand Image And Perception Of Products On The Purchase Decisions Of Matic Motorcycle In East Belitung - Ahmad Azmy; Dery Nauyoman; Muhammad Zakky (Jurnal Administrasi Bisnis, 2020)
This study aims to analyze the effect of brand image and product perception on purchasing decisions of automatic motorcycles in East Belitung. Motorbikes are vehicles that are in demand by consumers with a number of factors considering purchasing as needed. The object of this study analyzes how consumers consider a number of factors that serve as motorcycle purchasing decisions. This research was conducted for three months starting from August-October 2018. The location of the study was East Belitung with a total sample of 100 people. The variables used are brand image and product perception as an independent variable, while purchasing decisions as the dependent variable. The statistical method used to test data in this study is the method of multiple linear regression analysis. The results of this study are partially brand image has a significant influence on purchasing decisions, product perception has a significant influence on purchasing decisions. Simultaneously brand image and product perception have a joint influence on purchasing decisions.